2022
DOI: 10.3389/fendo.2022.967016
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of endoplasmic reticulum-related and secretome gene expression profiles in the progression of non-alcoholic fatty liver disease

Abstract: Endoplasmic reticulum (ER) is the principal organelle for protein synthesis, such as hepatokines and transmembrane proteins, and is critical for maintaining physiological function. Dysfunction of ER is associated with metabolic disorders. However, the role of ER homeostasis as well as hepatokines in the progression of non-alcoholic fatty liver disease (NAFLD) remains to be elucidated. Here we comprehensively analyzed the RNA-seq profiles of liver biopsies from 206 NAFLD patients and 10 controls from dataset GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…According to the KEGG and GO analysis results of DEGs and susceptibility gene module, ECM seems to play an important role in the development of NAFLD. This finding is consistent with several previous studies 22 23 24 . BMs themselves are a unique form of ECM that mainly exist under endothelial and epithelial cells 3 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the KEGG and GO analysis results of DEGs and susceptibility gene module, ECM seems to play an important role in the development of NAFLD. This finding is consistent with several previous studies 22 23 24 . BMs themselves are a unique form of ECM that mainly exist under endothelial and epithelial cells 3 .…”
Section: Discussionsupporting
confidence: 94%
“…As a member of the extracellular glycoprotein family, LAMC3 is involved in a variety of biological processes, including maintenance of tissue structure, tissue differentiation and migration, as well as tumor invasion and metastasis [33]. Several previous studies on NAFLD-based transcriptome sequencing have also suggested that COL5A1 and LAMC3 might play important roles in NAFLD [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the rapid development of high-throughput sequencing technology and gene chip technology, more and more researchers are actively pursuing molecular markers using data mining and analysis of sequencing data or gene chips to the diagnosis and treatment of disease ( 19 , 43 , 44 ). In our study, we analyzed gene expression profiles of NASH patients and normal controls from five independent GEO data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating multi-omics approaches including genomics, transcriptomics, proteomics and metabolomics have provided additional insights (12)(13)(14)(15), which may not be elucidated by genomics analysis alone. In addition, previous bioinformatics analyses in cross-sectional studies have facilitated the exploration of potential biomarkers related to NAFLD/NASH (16)(17)(18)(19). However, for complex disease trait, the comprehensive molecular characterization of NASH are still not entirely deciphered.…”
Section: Introductionmentioning
confidence: 99%
“…This protein plays a critical role in inflammation and is implicated in the initiation and progression of cancer. Studies suggested that both QSOX1 and IL1RAP hold promise as potential biomarkers of NAFLD or obesity (17, 18).…”
Section: Introductionmentioning
confidence: 99%